2014
DOI: 10.1002/per.1975
|View full text |Cite
|
Sign up to set email alerts
|

Bifactor Models of Personality and College Student Performance: A Broad versus Narrow View

Abstract: Research in the area of personality traits and academic performance has been supported by consistent meta-analytic evidence demonstrating positive relationships between Conscientiousness and grade point average (GPA). However, academic performance is not solely a function of GPA but also a number of other important intellectual, interpersonal and intrapersonal behaviours. This wider criterion space opens up the possibility for many personality factors and their underlying facets to relate to academic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 76 publications
(168 reference statements)
3
69
0
1
Order By: Relevance
“…Observed correlations may be inflated or attenuated as estimates of relations between the broad/narrow psychopathology constructs and other variables (83). For example, the perfectionism facet of Conscientiousness was negatively related to university student physical and mental health after controlling for general Conscientiousness; this relationship was obscured when both sources of variance were combined in the observed subscale score (84). By separating the predictive power of broad and narrow factors, bifactor modeling can provide a clearer picture of the nomological network of psychopathology.…”
Section: Relations Of General and Group Factors With External Variablesmentioning
confidence: 99%
“…Observed correlations may be inflated or attenuated as estimates of relations between the broad/narrow psychopathology constructs and other variables (83). For example, the perfectionism facet of Conscientiousness was negatively related to university student physical and mental health after controlling for general Conscientiousness; this relationship was obscured when both sources of variance were combined in the observed subscale score (84). By separating the predictive power of broad and narrow factors, bifactor modeling can provide a clearer picture of the nomological network of psychopathology.…”
Section: Relations Of General and Group Factors With External Variablesmentioning
confidence: 99%
“…Residualised facets is the most extreme in that it assigns all common variance to the broad traits. In contrast, the bifactor model (Chen, Hayes, Carver, Laurenceau, & Zhang, ; McAbee, Oswald, & Connelly, ; Perera, Izadikhah, O’Connor, & McIlveen, ) distributes common variance between factors and facets. The bifactor model also provides a way of separating evaluative variance from more descriptive trait variance (Anglim, Morse, et al, ).…”
Section: Recommendations For Researchersmentioning
confidence: 99%
“…In a bifactor model, each indicator loads on the general factor (which influences all measures) and a specific factor (which influences some measures). In fitting a bifactor SEM, ideally, multiple indicators for each specific factor are used (e.g., multiple items from each scale of a personality measure; McAbee, Oswald, & Connelly, 2014). A bifactor model of Edwards et al's (2008) data is shown in Figure 1.…”
Section: Bifactor Modelmentioning
confidence: 99%